SARS-CoV-2-Induced Remission of Chemotherapy Resistance B-Cell Non-Hodgkin Lymphoma: A Case Report - Yan Xiao; Jinwei Wang; Kai Yang; Meiling Jiang; Bo Zhang (Case Reports in Oncology)
Introduction: Investigation on virus-host interaction may provide new clues for antitumor immunotherapy. Case Presentation: In this case report, we describe an unusual case of B-cell non-Hodgkin lymphoma in an aged woman who recovered following SARS-COV-2 infection. We discuss the case and suggest that virus induced cross-reactivity against tumor account for the remission. Conclusion: Mapping epitope characteristics on B cell non-Hodgkin lymphoma antigen and on SARS-COV-2 antigen may provide much needed information for antigen based antitumor immune therapy in the future.